Pengaruh Loan to Deposit Ratio (LDR) Terhadap Return on Asset (ROA) Pada PT. Bank Central Asia, Tbk. - Maya, Mayadah; Muniarty, Puji (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2024)
This research was conducted at PT. Bank Central Asia, Tbk. With th aim of knowing and analyzing the of banks with LDR and ROA ratios and looking for their influence LDR on ROA. The research method used is associative quantitative research. The sample for this study consistend of balance sheets, income statements and notes to financial statements (CALK) for 10 years from the period 2013 - 2022 with the sampling technique used being purposive sampling. The analytical used are simple linear regressin, simple correlation, Coefficient of Determination and t-test which aims to analyze the relationship between variables LDR on ROA using SPSS v software. 22.the results of this study indicate that LDR the effect is not significant on ROA.